Preliminary examination of validity and reliability of athlete-specific sleep questionnaires for undergraduate athletes in Singapore - Yeep, Jun Hui (2019)
The validity and reliability of existing athlete-specific sleep questionnaires have not been examined for non-Western undergraduate athletes. The purpose of this study was to preliminarily examine if the Athlete Sleep Behavior Questionnaire (ABSQ) and the Athlete Sleep Screening Questionnaire (ASSQ) are reliable and valid sleep measures for Singaporean undergraduate athletes. 200 participants (100 athletes, 100 non-athletes) completed the ASBQ, the ASSQ as well as three well-established sleep questionnaires; the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI) and the Sleep Hygiene Index (SHI). The Subjective Vitality Scale (SVS) was also completed. The ASBQ, the PSQI and the SHI were statistically significant predictors of subjective vitality (beta = 0.259, -0.283, -0.630 respectively) for the athlete group. Statistically significant differences between athletes and non-athletes were observed for the ASBQ global scores (40±0.8 vs. 36±0.8 respectively) and the SHI global scores (18±0.7 vs. 16±0.7 respectively) but not for the ASSQ, the ESS or the PSQI. Sleep questionnaires offers a convenient and practical solution in finding out the key issues that undergraduate athletes face with regards to sleep. The ASBQ and the SHI may be used concurrently when implementing sleep-hygiene interventions to improve the sleep habits of undergraduate athletes.